Analgesia after Cesarean Delivery: Patient Evaluations and Costs of Five Opioid Techniques. Issue 3 (May 1991) - Cohen, Sheila E.; Halpern, Jerry; Subak, Leslee L.; Brose, William G.
Abstract : The study was designed to compare five opioid analgesic regimens administered after cesarean delivery in a routine hospital setting with respect to patients' perceptions of their pain relief and the impact of analgesic technique on recovery and hospital costs. After cesarean delivery, 684 patients received one of the following: epidural morphine, alone (EM, n = 128), or with fentanyl (EM + F, n = 245); subarachnoid morphine ( n = 48); intramuscular meperidine ( n = 165), or patient-controlled analgesia using meperidine (PCA, n = 98). On the first three postoperative days (Days 1-3; day of operation is Day 1) patients were surveyed regarding their impressions of their analgesia, the incidence of side effects, times to resume normal activities and satisfaction with their technique. Information regarding drug interventions and costs was obtained from anesthetic records and nursing charts. Patients receiving intramuscular and PCA opioids reported significantly more severe pain during the first 16 hours than those receiving intraspinal opioids ( p < 0.05); differences were minimal for the remainder of Day 1. Among the intraspinal groups, analgesia was best overall with EM; specifically, fentanyl did not decrease early postoperative pain. Analgesia with PCA and intramuscular opioids was similar during the first 16 hours; however, PCA patients felt they had less pain thereafter. Side effects were common in all intraspinal groups and were least frequent with PCA ( p < 0.05 versus all intraspinal groups). Times to sit, walk and drink were similar in all patients except those receiving intramuscular opioids after general anesthesia, who experienced a several-hour delay. Other aspects of recovery did not differ among the groups. Satisfaction parallelled pain relief and was better with intraspinal than with systemic opioids. Costs were greatest with PCA, although differences were small (<1%) relative to total hospital charges.